Multimodality in internet news media (Open Herald: Periodical of Methodical Research, 2024)
This article examines the role of multimodality in internet news media, highlighting the integration of text, images, audio, and video in news storytelling. It explores the evolution of news media from traditional print to digital platforms, emphasizing the impact of digital technology on journalistic practices. Through case studies of leading news websites, the article illustrates how multimodal elements enhance audience engagement and interaction. It discusses the challenges and opportunities presented by multimodality, including technical complexities and the potential for future advancements. The findings suggest that multimodality has fundamentally transformed news media, offering a more dynamic, interactive, and engaging experience for audiences. This shift underscores the importance of understanding and adapting to multimodal communication strategies in the digital age.